Barriers to blood donation on social media: An analysis of Facebook and Twitter posts. Issue 10 (8th August 2020) - Ramondt, Steven; Zijlstra, Melissa; Kerkhof, Peter; Merz, Eva‐Maria
Abstract: Background: To better understand donor behavior and ensure a safe and sufficient blood supply, various observational studies have examined barriers to blood donation. This study used Facebook and Twitter data to enhance existing research on donation barriers and associated emotions communicated on social media by both donors and non‐donors. Study design and methods: We conducted a semantic network analysis (SNA) with 168 232 public Dutch language social media messages from Facebook and Twitter during 2012‐2018. SNA uses concepts as nodes in a network and the relationship (ie, co‐occurrence) as links between them. We identified the relationship between donation barriers, non‐donation (voluntary and involuntary), and dissatisfaction (anger and disappointment) within social media messages. This computational method was combined with an analysis examining significant relationships in‐depth. Results: Twelve donation barriers were identified: lifestyle, donation location, medical reasons, no invitation, opening times, physical reactions, pregnancy, remuneration, sexual risk behavior, time constraints, travels, and waiting times. More messages related to involuntary non‐donation compared to voluntary non‐donation. Involuntary non‐donation was associated most strongly with medical reasons and sexual risk behavior, while voluntary non‐donation was associated most strongly with resentment regarding remuneration of the blood bankʼs top management. Anger associated most strongly with sexual risk behavior and disappointment most strongly with medical reasons. Conclusion: Discussions around blood donation are increasingly taking place online. Donation barriers found in this study differ from those in survey research. Insights into how donation barriers are communicated in an ever‐growing online environment can be utilized to enhance recruitment and retention strategies.